Endodontic treatment in patients with X-linked hypophosphatemic rickets - Cleverton Roberto de Andrade; Cláudio Maranhão Pereira; Fabio Augusto Ito; Ricardo Della Coletta; Edgard Graner; Marcio Ajudarte Lopes (Universidade Estadual de Campinas, 2015)
The X-linked hypophosphatemic rickets (XLHR) is the most common type of rickets in developed countries, with an incidence of 1- 20.000 individuals. It results from a defect in renal tubular phosphate transport, which leads to a hypophosphatemia. This alteration is responsible for abnormalities of bones and decreased dental mineralization. One of the most important buccal alteration is periapical and/or periodontal abscess without caries or trauma. We reported one case of XLHR that sought our department for dental treatment. The patient presented generalized periodontal disease and radiolucent images at the periapical regions of lateral superior incisors and first and second superior molars. Periodontal and endodontic treatments were performed, being the last one with successive curative changes of calcium hydroxide and filling with molded gutta-percha cones. The patient is in follow-up being examined routinely without presenting alterations.